2011
DOI: 10.2466/06.10.13.pr0.109.5.453-460
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time Physical Activity and Psychological Well-Being in University Students

Abstract: An analysis of psychological well-being (self-esteem and subjective vitality) of 639 Spanish university students was performed, while accounting for the amount of leisure-time physical activity. The Spanish versions of the Rosenberg Self-Esteem Scale and Subjective Vitality Scale were employed. Participants were divided into four groups (Low, Moderate, High, and Very high) depending on estimation of energy expenditure in leisure-time physical activity. Men and women having higher physical activity rated higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 19 publications
(21 reference statements)
4
34
0
5
Order By: Relevance
“…For example, when applied to illbeing, reductions in depressive symptomology were associated with exercise intensity as opposed to the frequency or duration of exercise (Craft & Landers, 1998;Dunn, Trivedi, Kampert, Clark, & Chambliss, 2005). Building on these findings, a number of researchers (e.g., Cerin et al, 2009;Molina-García, Castillo, & Queralt, 2011;Netz et al, 2005) have noted that the intensity of HEPA may play a unique role in predicting markers of well-being, especially when the strenuous nature of engagement is selected by the individual (i.e., it is volitional) as opposed to being imposed by others (Ekkekakis, Parfitt, & Petruzzello, 2011). Nevertheless, it is also noteworthy that Cerin et al (2009) found positive associations between frequency and amount (i.e., duration) of leisure-time HEPA and well-being.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, when applied to illbeing, reductions in depressive symptomology were associated with exercise intensity as opposed to the frequency or duration of exercise (Craft & Landers, 1998;Dunn, Trivedi, Kampert, Clark, & Chambliss, 2005). Building on these findings, a number of researchers (e.g., Cerin et al, 2009;Molina-García, Castillo, & Queralt, 2011;Netz et al, 2005) have noted that the intensity of HEPA may play a unique role in predicting markers of well-being, especially when the strenuous nature of engagement is selected by the individual (i.e., it is volitional) as opposed to being imposed by others (Ekkekakis, Parfitt, & Petruzzello, 2011). Nevertheless, it is also noteworthy that Cerin et al (2009) found positive associations between frequency and amount (i.e., duration) of leisure-time HEPA and well-being.…”
Section: Introductionmentioning
confidence: 92%
“…However, conclusions regarding psychological need satisfaction and well-being advanced by Gunnell et al (2011) and Mack et al (2012) were based on amalgamated physical activity scores. We aim to extend this line of inquiry to include the discrete components of HEPA which may be particularly salient given recent findings suggestive of the unique role afforded to physical activity intensity in relation to increases in well-being (Cerin et al, 2009;Molina-García et al, 2011;Netz et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…É possível que esse predomínio esteja relacionado à maior facilidade de mensuração da atividade, por exemplo, em termos do número de horas e vezes por semana que a atividade física pode ser descrita. Outra possibilidade é que, como a prática esportiva tem sido associada a benefícios atribuídos aos efeitos fisiológicos sobre o corpo humano, acabe sendo mais estudada [18][19][20][21][22][23] .…”
Section: Resultsunclassified
“…O futebol tem grande influência da cultura nacional, enquanto caminhada e/ou corrida são práticas corporais que não necessitam de grandes investimentos financeiros, e com benefícios para saúde física e mental. Entretanto, o gênero ainda tem sido uma variável significativa, visto que homens tendem a praticar mais tais modalidades que mulheres 18,19,23 .…”
Section: Resultsunclassified
“…La vinculación entre las ciencias del movimiento humano y la psicología positiva es un área de estudio relativamente incipiente. En esta línea se encuentran estudios que documentan los estados de flow (fluir como un estado de disfrute asociado con estar inmerso en la tarea) (Elbe, Strahler, Krustrup, Wikman, & Stelter, 2010;Kawabata & Mallett, 2011), así como estados percibidos de bienestar asociados con la práctica de ejercicio en el tiempo libre (Hyde, Conroy, Pincus, & Ram, 2011) y mayores índices de vitalidad subjetiva asociados a mayores niveles de actividad física (Molina-García, Castillo, & Queralt, 2011).…”
unclassified